Kinetic modelling of Dihydroxystearic Acid (DHSA) production from palm kernel oil-based oleic acid / Abdul Hakim Masu'ud Fathi and Siti Khatijah Jamaludin - Fathi, Abdul Hakim Masu'ud; Jamaludin, Siti Khatijah (2020)
Dihydroxystearic Acid (DHSA) is a chemical compound that belongs in the hydroxy fatty acid group which is mainly used in cosmetic industries. DHSA usually produced by the process of in-situ epoxidation of oleic acid, followed by the hydrolysis of the epoxidized oleic acid. This study focuses on the kinetic modelling of the production of DHSA. The purpose of this study is to establish a kinetic model of one-pot synthesis of DHSA via continuous in-situ epoxidation and hydrolysis process and to fit the kinetic model with the experimental data to obtain the reaction rate constants (k) and activation energy (Ea). Assumptions was made which then applied to the reaction scheme in order to develop a new reaction scheme for the kinetic model. MATLAB was the software used for developing the model where ODE45 function in MATLAB were used to solve the ordinary differential equation (ODE) by applying fourth-order Runge-Kutta method. From the model, reaction rate constants (k) were determined. The reaction rate constants (k) determined were then used to obtain the activation energy (Ea) of the reaction by constructing the Arrhenius plot for the reaction at temperature 55C and 75C.